Research Mediation in Education: A Typology of Research Brokering Organizations That Exist Across Canada - Cooper, Amanda Mae (Alberta Journal of Educational Research, 2014)
This paper explores the increasingly prominent role of research brokering organizations (RBOs) in strengthening connections between education research, policy and practice across Canada. This paper is organized in three sections. First, it provides a literature review of research mediation– exploring terminology, models and empirical work (albeit sparse) across health, business, education sectors. The second section provides three conceptual contributions to the field: RBOs’ roles in knowledge mobilization occurring in the white space of broader public service systems, a typology of Canadian RBOs that exist in education using four broad categories: governmental, not-for-profit, for-profit and membership RBOs, and a knowledge brokering framework along seven dimensions: mission, resources, staff roles, political affiliation, autonomy, message and linkages. The third section provides empirical data about the frequency and types of RBOs that exist across Canada. Cet article explore le rôle de plus en plus important que jouent les organismes de médiation de la recherche dans la consolidation des liens entre les politiques et la pratique en matière de recherche en éducation partout au Canada. L’article se divise en trois sections. D’abord, on y présente une revue de la littérature portant sur la médiation de la recherche et évoquant la terminologie, les modèles et le travail empirique (quoique limités) qui touchent les secteurs de la santé, des affaires et de l’éducation. La deuxième section contribue trois concepts au domaine : les rôles que jouent les organismes de médiation de la recherche dans la mobilisation des connaissances dans les « espaces vides » de la fonction publique en général; une typologie des organismes canadiens de médiation de la recherche en éducation selon quatre grandes catégories (gouvernemental, sans but lucratif, à but lucratif et composé de membres) et un cadre portant sur la médiation de la recherche et axé sur sept dimensions (mission, ressources, rôles du personnel, affiliation politique, autonomie, messages et liens). La troisième section offre des données empiriques sur la fréquence et les types d’organismes de médiation de la recherche qui existent au Canada.